2016
DOI: 10.1016/j.juro.2015.07.113
|View full text |Cite
|
Sign up to set email alerts
|

Clear Cell Renal Cell Carcinoma Subtypes Identified by BAP1 and PBRM1 Expression

Abstract: Purpose In clear cell renal cell carcinoma BAP1 and PBRM1 are 2 of the most commonly mutated genes (10% to 15% and 40% to 50%, respectively). We sought to determine the prognostic significance of PBRM1 and BAP1 expression in clear cell renal cell carcinoma. Materials and Methods We used immunohistochemistry to assess PBRM1 protein expression in 1,479 primary clear cell renal cell carcinoma tumors that were previously stained for BAP1. A centralized pathologist reviewed all cases and categorized tumors as pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
86
2
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 20 publications
(32 reference statements)
6
86
2
4
Order By: Relevance
“…Previously published studies have reported a more aggressive clinical course and worse prognosis in patients who have ccRCC with BAP1 mutations [11,15]. In this investigation, BAP1 mutations were associated with increased risk of cancer-specific death, but the association did not retain significance on inclusion of the SSIGN score in a multivariable model.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Previously published studies have reported a more aggressive clinical course and worse prognosis in patients who have ccRCC with BAP1 mutations [11,15]. In this investigation, BAP1 mutations were associated with increased risk of cancer-specific death, but the association did not retain significance on inclusion of the SSIGN score in a multivariable model.…”
Section: Discussioncontrasting
confidence: 52%
“…A number of previous investigations have sought to identify prognostic biomarkers in ccRCC, and several studies focused on recurrently mutated genes along with cytogenetic alterations [10,11,15,2124] in isolated cohorts. Many of the molecular biomarkers assessed in previous studies offered little or no advantage over more traditional pathologic and clinical variables in the prediction of clinical outcomes [11,21].…”
Section: Discussionmentioning
confidence: 99%
“…Most PBRM1 mutations are inactivating and loss of expression is associated with an increase in cell proliferation and migration 14 , whereas its reintroduction reduces cell proliferation and is associated with G1 cell cycle arrest induced by an increase in p21 CIP1 (REFS 144,145). Reports of PBRM1 expression levels in RCC and of its association with poor patient survival are contradictory 146,147 . The precise mechanisms that underlie the oncogenic contribution of PBRM1 mutations in RCC remain to be clarified; however, in addition to its role in regulating genes that control proliferation, such as p21 CIP1 , PBRM1 also regulates the expression of cell-adhesion and cell-signalling molecules such as E-cadherin [148][149][150] (and as such, the subcellular distribution of β-catenin) as well as sister chromatid cohesion 151 .…”
Section: Histone Modification In Rccmentioning
confidence: 99%
“…Not surprisingly, several other recurrently mutated genes in ccRCC—including polybromo 1 ( PBRM1 ), SET domain containing 2 ( SETD2 ), and BRCA1 associated protein 1 ( BAP1 )—are also located on chromosome 3p [9, 10]. The stratification of patients with ccRCC on the basis of mutations in BAP1 and PBRM1 has been shown to correlate with clinical outcomes in localized disease [11, 1923]. Currently, however, these biomarkers have not significantly improved the clinical stratification of patients beyond traditional clinical and pathologic variables [4, 9, 1828].…”
Section: Introductionmentioning
confidence: 99%